Human Resource Development Strategy In Facing Digital Transformation - Dwiwarman, Denny Aditya (Universitas Dharma Wacana, 2024)
This research was conducted at PT. Aruman Aditya which operates in the developer sector with the aim of this research being to develop appropriate HR management strategies to support digital transformation in improving company results where human resource management requires a strategic management style to achieve sustainable competitive advantage by create education and training programs. Methodology study use qualitative approach, observation structured and SWOT analysis. The results of the research show that the educational methods used by company leaders are in developing human resources in facing transformation The company's digital implementation is still being pursued and the company owner advises management to take action to create a programmed and sustainable education program to increase knowledge and skills in accordance with digital- based work needs , while training methods in the process of developing human resources in facing digital transformation have not yet been programmed.